"Where you do it" matters: The impact of hotels' revenue-management implementation strategies on performance. (October 2017) - Altin, Mehmet; Schwartz, Zvi; Uysal, Muzaffer
Highlights: First empirical study to compare the performance of various hotel revenue-management implementation strategies. Random sample of 602 hotels, self-reported implementation strategy, performances measured using hotel's RevPAR index. Used four different time periods: last month, 3, 6, and 12 months' averages. Chi-square test, repeated measure ANOVA, pairwise comparison and multiple regression analysis. Findings suggest that not all strategies are equally effective, some are clearly better than others. Abstract: This study explores RM strategic implementation approaches, addressing the question of whether the RM function should be performed within the hotel property, or should be outsourced to an outside entity such as corporate, regional office or a third party. Using a random sample of 602 US hotels, the study analyzed the hotels' RevPAR Index over varying periods and the hotels' self-reported RM implementation strategy. The findings suggest that hotel characteristics such as size and scale affect their decision on where to perform the RM function. More importantly, we find that this strategic implementation decision impact the hotel's level of performance compared to its competitive set: corporate and centralized RM functions outperform in-house and third party. Interestingly, the findings indicate that a mixed strategy, one that combines implementation strategies, is associated with the highest RevPAR index.